![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
ababab : ( ab x 3 ) - 1351
= ( 1351 x 3 ) - ( ababab : ab )
= 4053 - 111
= 3942
![](https://rs.olm.vn/images/avt/0.png?1311)
ababab : ( ab * 3 )
= ababab : ab : 3
= ab * 10101 : ab : 3
= ( ab : ab ) * ( 10101 : 3 )
= 1 * 3367 = 3367
Vậy ababab : ( ab * 3 ) = 3367
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
A = ababab : ( 39 x ab ) +1758
A = ab x 10101 : 39 : ab + 1758
A = ( ab : ab ) x ( 10101 : 39 ) + 1758
A = 1 x 259 + 1758
A = 2017
![](https://rs.olm.vn/images/avt/0.png?1311)
Xét abba
abba = 1001a + 110b = 11(91a + 10b) chia hết cho 11
Xét aaabbb:
aaabbb = 111000a + 111b = 37(3000a + 3) chia hết cho 37
Xét ababab
ababab = 101010a + 10101b = 7(14430a + 1443b) chia hết cho 7
Xét abab - baba
abab - baba = 1010a + 101b - 1010b - 101a = (1010a - 101a) - (1010b - 101b) = 909a - 909b = 909(a - b) chia hết cho 9